FEATURES AND FACTORS OF DEVELOPMENT OF REGIONAL MARKETS OF POULTRY PRODUCTS IN UKRAINE - ULYCH, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The poultry market remains strategically important for Ukraine, with great potential for growth and adaptation to global challenges. The purpose of the article is to study the features and factors of the development of regional markets for poultry products in Ukraine. The results of the analysis revealed the main features of the modern development of regional poultry markets in Ukraine and emphasized its spatial asymmetry. It was found that the period 2018-2020 was a turning point for the industry: market consolidation, a change in the structure of production, export development, and adaptation to global challenges took place. The main influencing factors were export policy, currency fluctuations, rising feed costs, and the COVID-19 pandemic. Despite the difficulties, the poultry market remained one of Ukraine’s most stable agricultural sectors. It has been proven that the poultry market in Ukraine is undergoing significant changes due to economic, environmental, and social factors. Global crises, currency fluctuations, and changes in consumer preferences have a significant impact, forcing producers to adapt their business models. The dominance of extensive agricultural holdings creates challenges for small and medium-sized enterprises, but interest in farm and organic products is growing. Sustainable industry development requires introducing environmentally friendly technologies, reducing environmental impact, and optimizing logistics. Finding alternative feed resources, reducing waste, and implementing energy-efficient solutions is important. Global trends in sustainable development require the ecological modernization of production, the introduction of energy-efficient technologies, and the minimization of adverse environmental impact.